Analisis Pengelolaan Alokasi Dana Desa Dalam Pembangunan Desa (Studi Kasus: Desa Minta Kasih, Kecamatan Salapian, Kabupaten Langkat) - Dela Syakillah Nuraisah Br Bancin; Nur Fadhilah Ahmad Hasibuan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
This study aims to analyze the management of village fund allocation in village development and identify factors that encourage and hinder its implementation. The research method used is a qualitative descriptive approach, with a case study conducted in Minta Kasih Village located in Salapian District, Langkat Regency. In this study, researchers analyzed the implementation of village fund allocation and its impact on village community empowerment. The research approach includes interviews, observations and document analysis to obtain information on the use of village fund allocation. The results showed several obstacles in accountability for village fund allocation, especially related to reporting and monitoring. In addition, there are gaps in community accessibility and understanding of village fund allocation programs that have the potential to affect the effectiveness of village development. From the results of the study, it is known that the factors that support the implementation of village fund allocation in the development of Minta Kasih Village are community support in infrastructure development, education, health, and the development of micro and small enterprises in the village. However, inhibiting factors include the government's inability to optimize budget use and delays in preparing village fund allocation accountability reports (ADD).